2012
DOI: 10.1108/17440081211258169
|View full text |Cite
|
Sign up to set email alerts
|

Semantic approach to travel information search and itinerary recommendation

Abstract: Purpose -The growth of online data and services on the Web have have led to the Web become an indispensable tool for the tourist industry. It is not denied that various approaches bring benefits for visitors, in supporting their searching for tourist attractions, such as interesting places for the visit, eating or staying. However, like a coin has two sides, too much information would present a difficulty for people when planning their journeys. Generally, tourists usually have problems when trying to find sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Hattori and Nadamoto (2013) aims to propose a method to extract tip information that has been classified by topic from social networking services as a first step in extracting tip information from social media. Cao and Nguyen (2012) proposes a semantic approach for searching tourist information and generating travel itinerary and Tabatabaei et al (2010) an approach to achieve security conscious composition of semantic web services. To deal with large‐scale RDF data, it is important to develop a scheme which enables the processing of large RDF data in an efficient manner (Ohsawa et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hattori and Nadamoto (2013) aims to propose a method to extract tip information that has been classified by topic from social networking services as a first step in extracting tip information from social media. Cao and Nguyen (2012) proposes a semantic approach for searching tourist information and generating travel itinerary and Tabatabaei et al (2010) an approach to achieve security conscious composition of semantic web services. To deal with large‐scale RDF data, it is important to develop a scheme which enables the processing of large RDF data in an efficient manner (Ohsawa et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results concluded that the proposed algorithm can get better performances by investigating from travel logs. Cao and Nguyen [183] presented a novel semantic algorithm for a travel itinerary recommendation system. Ontology was collected from linked data for filtering semantic of the user interests.…”
Section: ) Ontology-based Recommendationsmentioning
confidence: 99%
“…The author has also developed a Semantic Tourist Action Access and Recommending System called STAAR [7]. The main focus of this system is to help a tourist find relevant information for his trip through Web and smartphone.…”
Section: Related Workmentioning
confidence: 99%